Clinical Manual for Medical Students (University of Maribor Press, 2016)
Clinical Manual was created for medical students who variously meet with the patients in the hospital setting (Internal Medicine, Surgery, Paediatrics, Otorhinolaryngology, Psychiatry, Ophthalmology, Neurology, Dermatovenerology, Gynaecology, Infections, Urgent Medicine, Family Medicine). Clinical skills of taking medical history, performing physical examination and other clinical skills described in the manual (interpretation of the ecg, the x-ray scan of the thorax, acid base balance; writing a prescription, a referral, a work order; arterial blood sampling, urinary bladder catheterization, peripheral venous cannulation, digital rectal examination) are vital for successful determination of the final diagnosis. Clinical Manual is written as a reminder and is not a substitution for the literature of the chosen fields of medicine. It serves as an accessory to successfully approach to the patients. It encourages the students to refresh, deepen and critically evaluate their knowledge and to be correctly educated by their mentors for performing the protocols written in the manual.